The Effect of Ripening on the Titration Results of the Ethylene Content of Kepok Banana Peel (Musa paradisiaca L.) - Charloq, Charloq (JURNAL AGROPLASMA, 2024)
Bananas are one of the climacteric fruits Ethylene is a hormone that play a role in the fruit ripening process during the climacteric phase, to accelerate the ripening process of fruit, to be utilized as a stimulant latex for rubber plants. This study aims to utilize banana peel waste (Musa paradisiaca L.) as a source of ethylene. This study used a completely randomized design (CRD) non-factorial that is, green banana skin with ripening 0, 1, 2, 3 days, yellowish green banana peel with ripening 0, 1, 2, 3 days, yellow banana skin with ripening 0, 1,2,3 days. This research was conducted by titration method which was repeated three times. The results showed that the highest ethylene content was found in yellow banana peels with 1 day ripening. Keywords: ethylene, banana peel color, ripening time